PERAN BRAND EXPERIENCE, BRAND IMAGE, BRAND VALUE, DAN CUSTOMER SATISFACTION TERHADAP BRAND LOYALTY PADA PELANGGAN COFFESHOP - Wuryan, Sophiyanto; Ardyawati, Ananda Indhira (JURNAL LENTERA BISNIS, 2026)
This study aims to analyze the influence of Brand Experience, Brand Image, Brand Value, and Customer Satisfaction on Brand Loyalty among customers of Fore Coffee at Hive Harapan Indah, Bekasi. The research employed a quantitative approach, with data collected through questionnaires distributed to 105 active customers of Fore Coffee. Data were analyzed using multiple linear regression with the help of SPSS. The findings indicate that all four independent variables Brand Experience, Brand Image, Brand Value, and Customer Satisfaction have a positive and significant effect on Brand Loyalty, both simultaneously and. This research contributes theoretically to marketing literature, particularly in the context of the coffee shop industry in Indonesia, and offers practical implications for Fore Coffee’s management in developing marketing strategies focused on customer experience and satisfaction.